2018
DOI: 10.1126/science.aau1044
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing and discovering cellular structures with super-resolution microscopy

Abstract: Super-resolution microscopy has overcome a long-held resolution barrier-the diffraction limit-in light microscopy and enabled visualization of previously invisible molecular details in biological systems. Since their conception, super-resolution imaging methods have continually evolved and can now be used to image cellular structures in three dimensions, multiple colors, and living systems with nanometer-scale resolution. These methods have been applied to answer questions involving the organization, interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
418
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(420 citation statements)
references
References 101 publications
2
418
0
Order By: Relevance
“…To investigate cytoskeletal changes at the ultrastructural level, we fixed the cells for immunofluorescence labeling, and performed 3D-STORM SRM to achieve ≈20 nm spatial resolution optically. [23][24][25][26][27] Notably, 3D-STORM revealed substantial ultrastructural changes in the vimentin intermediate filaments ( Figure 1A,B and Figure S2A, Supporting Information), whereas conventional, diffraction-limited microscopy did not well resolve the filaments ( Figure 1B). For the milder treatment of 50% HBSS buffer, where changes in cell morphology were moderate ( Figure S1A, Supporting Information), 3D-STORM showed that the initially long and continuous vimentin filaments, which often ran through the entire cell lengths, all broke down into short segments a few micrometers in length ( Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate cytoskeletal changes at the ultrastructural level, we fixed the cells for immunofluorescence labeling, and performed 3D-STORM SRM to achieve ≈20 nm spatial resolution optically. [23][24][25][26][27] Notably, 3D-STORM revealed substantial ultrastructural changes in the vimentin intermediate filaments ( Figure 1A,B and Figure S2A, Supporting Information), whereas conventional, diffraction-limited microscopy did not well resolve the filaments ( Figure 1B). For the milder treatment of 50% HBSS buffer, where changes in cell morphology were moderate ( Figure S1A, Supporting Information), 3D-STORM showed that the initially long and continuous vimentin filaments, which often ran through the entire cell lengths, all broke down into short segments a few micrometers in length ( Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering electron microscopy (EM) studies have revealed parallel arrays of microtubules within axons that support vesicular transport over long distances (Peters et al, 1991). Only recently has optical super-resolution microscopy been able to unveil striking actin assemblies within axons (Papandréou and Leterrier, 2018;Sigal et al, 2018): the axon is lined by a membrane-associated periodic scaffold (MPS) composed of circumferential actin rings spaced every ~185 nm by tetramers of spectrins (D'Este et al, 2015;Leterrier et al, 2015;Xu et al, 2013;Zhong et al, 2014). A molecular and mechanistic understanding of actin rings and the MPS is still lacking, as EM has not yet visualized this assembly despite its presence in virtually all neurons (D'Este et al, 2016;Dubey et al, 2018;He et al, 2016;Unsain et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This study does not determine the precise subcellular protein localization in human endoneurial microvascular endothelial cells. Immunogold electron microscopy and super resolution microscopy provide avenues to more precisely determine the in situ subcellular localization of specific molecules restricted to the human BNB, particularly components of the restrictive intercellular junctional complex such as CLDN4, or determine the luminal or abluminal localization of transporters such as SLC1A1 prior to functional studies. This is an important future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogold electron microscopy and super resolution microscopy [46][47][48][49] ORCID Eroboghene E. Ubogu https://orcid.org/0000-0002-8307-9994…”
Section: Discussionmentioning
confidence: 99%